2007
DOI: 10.1111/j.1474-919x.2006.00621.x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal patterns of territory settlement and detectability in mated and unmated NightingalesLuscinia megarhynchos

Abstract: In many bird species the sex ratio of adults is male‐biased, which is likely to have consequences for the ecology as well as for the conservation of a species. For example, when some males remain unpaired in a population, there should be strong selection on behavioural traits that enhance pairing success. A surplus of males is also likely to have important implications for the interpretation of breeding bird survey data. In our study population of Nightingales Luscinia megarhynchos, about half of the males sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 41 publications
2
44
0
2
Order By: Relevance
“…20µPa). For clarity, interquartiles are given only for the male with the most and the male with the least variation of vocal sound pressure levels grounds are more successful in attracting a mate than males returning later from their winter quarters (Amrhein et al 2007). Schmidt et al (2008) looked at the spatial behaviour, and the singing activity of nightingales in response to conspecific playback and found that low-quality males (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…20µPa). For clarity, interquartiles are given only for the male with the most and the male with the least variation of vocal sound pressure levels grounds are more successful in attracting a mate than males returning later from their winter quarters (Amrhein et al 2007). Schmidt et al (2008) looked at the spatial behaviour, and the singing activity of nightingales in response to conspecific playback and found that low-quality males (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…This difference was not observed in the preliminary study . A number of migratory species are known to show a peak of singing activity earlier in the season , Amrhein et al 2007. Therefore, in the present study, the lower number of records for late May could be related to anomalous inhibition, as most males had already returned from their wintering areas ).…”
Section: Discussionmentioning
confidence: 60%
“…Curiosamente, el número de machos registrados durante la segunda quincena de mayo fue significativamente menor que durante el resto del periodo estudiado, lo que no coincide con el estudio preliminar, el cual mostró en estas mismas fechas un número de registros similar a la primera quincena de junio. Teniendo en cuenta que durante la segunda mitad de mayo la mayor parte de las tórtolas ya han llegado a sus territorios reproductivos ) y que el pico de actividad de muchas especies migratorias se produce a su llegada a las zonas de cría Amrhein et al 2007), es probable que el bajo número de registros estuviera ligado a una atípica menor actividad de canto de origen desconocido. En este sentido, durante los muestreos de la segunda mitad de mayo pudo observarse una fuerte bajada de temperaturas e inestabilidad meteorológica nocturna, lo que pudo inhibir considerablemente la actividad de canto de los machos Thomas, 1999;.…”
Section: Discussionunclassified
“…Uniquely, birds show adult male-skewed sex ratios (Donald 2007), a mechanism enhancing strong selection in the pairing success (Amrhein et al 2007). Our finding of males῎900 g at first capture being caught in more or less the same proportion (c 2 1 ῍2.98, P῍0.084) as females῎500 g in all trapping sessions (Fig.…”
Section: Discussionmentioning
confidence: 99%